Pembangunan pertanian dalam menentukan model pembangunan pertanian di desa Wonolopo - Hasan, Annisa Rahmah; Cahyatri, Divanissa Kusumoningrum; Ilham, Habib M.; Rusamsi, Leonardo Putra; Nugrahadi G, M. Rafif; Antriyandarti, Ernoiz (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2024)
Modernization is the process of transformation from traditional conditions towards more modern, developed, and prosperous states. This occurs across various aspects of community life, including rural areas. This research was conducted in Wonolopo Village with the aim of understanding its potential, issues, structural transformation, institutional transformation, and technological transfer. The research method utilized was descriptive analytics, gathering data through interviews. The research findings indicate that Wonolopo Village holds potential in the agricultural sector, particularly in rice and sugarcane cultivation. However, the main issue lies in fertilizer availability. Structural transformation occurs with each change of village leadership, while institutional transformation has been relatively limited in the past decade. Technological transfer has occurred, notably in the adoption of tractors in agriculture. Analysis of agricultural development models suggests the need for technological and institutional innovations to maximize Wonolopo Village's potential. The conclusion of this research underscores the importance of developing agricultural development models tailored to the village's conditions and potential, as well as the significance of collaboration with knowledgeable human resources. Recommendations include the necessity for improvement in village potential management and collaboration with more proficient human resources.